Chronological overview of municipal wastewater management concepts in focus of social changes - Márton (Studia Mundi – Economica, 2019)
For centuries, the amount and composition of communal and industrial wastewater has been constantly changing as a result of urbanization and the activities of modern society. Parallel to the emergence of cities, population density (/ person / km²) has also increased, which is not only important but also a necessity for wastewater treatment. Geographical conditions, infrastructure and industrialization also played a major role in the clustering of the population. The rivers and the wastage of rivers led to the depopulation of cities in ancient times, so the rational management of the natural water supply was the cornerstone of urbanization. In densely populated areas, large amounts of communal wastewater were generated, and the treatment of them was a constant challenge. With the change in the industrial production structure, the biochemical composition of wastewater has also changed. This study would like to draw attention to the relationship between population growth, water management and wastewater treatment and the complex issues of applied methods.